Qualidade da carne de frangos de corte submetidos a diferentes níveis de bagaço de uva na dieta - Schmitt, Janaina (2019)
The food industry generates a considerable amount of waste. These foods are a source of bioactive compounds, which is their reuse in interesting animal feed. In addition, the low cost of victory and the consequent reduction of production costs comes to contribute to the production and reuse of waste. The objective of this study was to evaluate the zootechnical performance and meat quality of broilers fed with increasing levels of dehydrated and ground grape pomace (BU) included in the diet. A total of 640 birds of the Cobb lineage were used in a completely randomized design with four treatments: BU 0 - conventional feed; BU 50 - conventional feed + 50 g/kg BU; BU 100 - conventional feed + 100 g/kg BU; BU 150 - conventional feed + 150 g/kg BU. The experimental period was 45 days and at the end were selected 4 birds per treatment and slaughtered for further laboratory analysis. The parameters of zootechnical performance measured were weight gain (GP), feed intake (CR) and feed conversion (CA). The meat quality was evaluated through centesimal composition, texture, fatty acid profile and monitoring of muscle pH, color stability and lipid oxidation under storage (1,4,7 and 10 days) under refrigeration. The results were submitted to statistical analysis through the SAS statistical program. Significant results (p ≤ 0.05) were found for the parameters of zootechnical performance, and the higher the supplementation with BU, the higher the CR and the AC and the lower the GP. The inclusion of BU also modified the lipid content, increasing the levels of C18: 2 n-6 and consequently increasing the content of polyunsaturated fatty acids. The values found for thiobarbituric acid reactive substances (TBARS) showed a significant effect (p ≤ 0.05) of inclusion of BU in the diet. In general, it can be concluded that supplementation with BU affected zootechnical performance, in the same way that it was shown to be able to promote the control of oxidative processes in chicken meat during storage under refrigeration.